Validating methods to infer mass changes from satellite gravity measurements using Synthetic Earth Gravity Modelling - Anjasmara, Ira Mutiara (Curtin University, 2013)
Leakage properties of isotropic and anisotropic filters used to recover mass changes from space gravity observations are studied. These are done through the use of gravity induced by simulated mass changes within a closed-loop validation procedure. Results show that the use of filter techniques can introduce significant errors introducing distortions between recovered and simulated mass. Previously not well known, the study revealed that leakage is dependent on the geographic location if the mass change considered.